2016
DOI: 10.1111/jai.13200
|View full text |Cite
|
Sign up to set email alerts
|

Energy acquisition and retention by age-0 and age-1 paddlefishPolyodon spathula(Walbaum, 1792) in relation to size, growth, and rearing conditions in two Great Plains reservoirs and hatchery ponds

Abstract: The objective of this study was to investigate lipid accumulation and storage in age-0 and age-1 paddlefish Polyodon spathula (Walbaum, 1792) in relation to age, stock,year, and growth. Juvenile paddlefish were collected from three locations in North Dakota and Montana, USA, during July and August of 2011 and 2012 and proximate analysis was used to determine lipid content. RNA/DNA ratios were used as an index of growth rates. Differences in age-based lipid accumulation and storage in juvenile paddlefish sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
2
3
1
Order By: Relevance
“…In contrast, those authors reported that mean and median lipid values were <1% during 2012, a lower water year resulting in a weaker year‐class. During 2014, the lipid values (mean and median values of 1.3% and 1.0%, respectively) for our largest category of wild‐caught fish (101–120 mm) were more comparable with the values from the weaker year‐class reported in Hemingway and Scarnecchia (). During 2015, however, our lipid values (mean and median values of 2.4% and 2.3%, respectively) were more comparable with the values from their exceptionally strong year‐class.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…In contrast, those authors reported that mean and median lipid values were <1% during 2012, a lower water year resulting in a weaker year‐class. During 2014, the lipid values (mean and median values of 1.3% and 1.0%, respectively) for our largest category of wild‐caught fish (101–120 mm) were more comparable with the values from the weaker year‐class reported in Hemingway and Scarnecchia (). During 2015, however, our lipid values (mean and median values of 2.4% and 2.3%, respectively) were more comparable with the values from their exceptionally strong year‐class.…”
Section: Discussionsupporting
confidence: 69%
“…During 2015, however, our lipid values (mean and median values of 2.4% and 2.3%, respectively) were more comparable with the values from their exceptionally strong year‐class. These comparisons may provide additional evidence that 2014 and 2015 could represent weak and strong year‐classes, respectively; however, the results of Hemingway and Scarnecchia () may not be directly comparable with our age‐0 sturgeon results in the lower Missouri River.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations